First Draft Genome Sequence of a Member of the Genus Mangrovibacter, Isolated from an Aquaculture Farm in India - Joseph, Toms C. (Genome Announc, 2014)
Mangrovibacter sp. MFB070, a Gram-negative, facultatively anaerobic, nitrogen-fixing bacterium, was isolated from an aquaculture farm in Cochin, India. Here, we report the first draft genome sequence of a member of the genus Mangrovibacter, which may help us to elucidate the evolutionary status of this genus. The draft genome sequence of the Mangrovibacter sp. consists of 5,361,682 bp, encoding 4,971 predicted coding sequences in 57 contigs.